PATHOMORPHOLOGICAL ALTERATIONS OF THE MYOCARDIUM IN INFANTS DURING THE FIRST YEAR OF LIFE - M.A, Urunova; M.E, Ernazarov (Research Focus International Scientific Journal, 2026)
This article analyzes pathomorphological changes of the myocardium in infants during the first year of life based on contemporary scientific literature. Published data indicate that during early ontogenesis the myocardium demonstrates increased sensitivity to hypoxia inflammatory processes, and hemodynamic disturbances. The literature review reveals that perinatal hypoxia and infectious factors contribute to cardiomyocyte gipertrofiya, interstitial edema, degenerative-dystrophic processes, and early fibrotic alterations. Structural remodeling of the myocardium is shown to be closely associated with microcirculatory impairment and cellular hypoxia. These findings substantiate the need for improving early diagnosis and preventive monitoring strategies.